Separation technologies for minerals, coal, and earth resources - Young, Courtney, 1962-; Luttrell, Gerald H. (Society for Mining, Metallurgy, and Exploration, 2012)
Separation Technologies for Minerals, Coal, and Earth Resources is an authoritative digest of the latest developments in the mineral processing industry. Dozens of authors share their insights on how practitioners can develop earth resources more economically while simultaneously addressing vital factors ranging from sustainability to environmental stewardship.
Keywords: Separation (Technology); Coal -- Cleaning.; elektronické knihy; electronic books